Orchestrating Sustainable Waste Management: A Pentahelix Collaborative Governance Model in Resource-Extraction Regions - Wahyudin, Wahyudin Noor; I Nyoman Sudayana; Heriamariaty; Johanna Maria Rotinsulu (Health and Technology Journal (HTechJ), 2026)
Rapid urbanization and aggressive mining and plantation expansions in East Barito Regency have severely complicated regional waste management systems. This study analyzes the strategic role of local government and identifies the critical factors that shape participatory policy models for designing an effective waste management framework. Researchers employed a mixed-methods sequential explanatory design integrating Structural Equation Modeling-Partial Least Squares, SWOT analysis, and the Analytic Hierarchy Process. Quantitative results demonstrate that environmental awareness, community participation, economic incentives, social dynamics, and private sector engagement significantly and positively influence sustainable waste management policies. Environmental factors emerge as the most dominant predictor of policy success within this specific industrial context. The local government functions simultaneously as a regulator, facilitator, coordinator, motivator, and evaluator to drive systemic transformation. Implementing community-based waste banks, circular economy initiatives, and Corporate Social Responsibility funding substantially amplifies active public participation. The research ultimately produces a novel participatory policy model grounded in collaborative governance and a comprehensive pentahelix approach. This integrated framework unites local authorities, residents, private enterprises, academics, and the media to deliver a sustainable waste management system tailored to resource-extraction regions. The proposed model provides actionable policy recommendations for regional authorities aiming to mitigate severe ecological deficits while fostering robust community empowerment and long-term environmental resilience.